(untitled) (International Journal of Nursing Education, 2019)
Introduction: Anemia is a very common problem in pediatric age group in many developing countries with an estimated prevalence of 43% of the World’s children. School children constitute 20.25% of total population in India and they are more vulnerable to this disease due to their rapid growth need of high iron. Method: Quantitative experimental approach with pre-test post-test design was adopted for the study. The main study was conducted among 90 tribal adolescent children, 60 from Govt, Aralam farm high school and 30 from government H.S.S Pala. The samples were selected by purposive sampling technique. The tools used were format for hemoglobin estimation, demographic Performa of the sample, knowledge questionnaire regarding anemia and structured teaching programme on anemia. Results: This study reveals that majority of tribal adolescent children were anaemic.61.1% of adolescent children had moderately adequate knowledge regarding anemia before the teaching programme and 76.6% had adequate knowledge regarding anemia after the teaching programme. The analysis of the data showed that the pre-test knowledge scores of the tribal adolescent children are significantly higher than that of post test scores (t=13.575, p<0.00).This emphasizes that the structured teaching programme was effective in improving the knowledge regarding anemia. Further, there was no significant association between the pretest knowledge scores and selected demographic variables. Conclusion: The study concluded that the structured teaching programme was effective in improving the knowledge of tribal adolescent children regarding anemia.